Comparative study of microsurgical lumbar discectomy and percutaneous endoscopic lumbar discectomy based on clinical outcome and muscle injury markers - Gautham Hanu; Silpa Thota; Venkat K; Ramesh Chandra V V; BCM Prasad; Siva Kumar Reddy; Geetanvita N; Indupriya E (Journal of Krishna Institute of Medical Sciences University, 2023)
Background: Lumbar Disc Herniation (LDH) is the most frequent entity affecting the spine resulting in low back pain and sciatica. Many minimally invasive procedures have been proposed for the treatment of LDH. Percutaneous Endoscopic Discectomy (PELD) is gaining popularity in recent years for the treatment of LDH and its supremacy over the well-established gold standard Microsurgical Lumbar Discectomy (MLD) is yet to be proven. Aim and Objectives: To compare pain relief using Visual Analogue Scale (VAS) score, Oswestry Disability Index (ODI), duration of surgery and incision length between MLD and PELD; To evaluate systemic cytokine response (CPK-CK, hs-CRP, IL-6) between MLD and PELD. Material and Methods: This was a prospective comparative analysis between MLD and PELD in patients undergoing surgery for single-level lumbar disc prolapse from January 2022 to October 2022 at a single institute. Results: The study included 64 patients, divided equally into two groups: 32 patients underwent conventional MLD, and 32 patients underwent PELD. Groups had similar demographic profiles and preoperative clinical features. Postoperatively, both groups showed significant improvements in pain (VAS) scores and functional disability (ODI), with no significant difference between the two groups. However, there were differences in certain biochemical markers: CPK and IL-6 levels were lower in the PELD group compared to the MLD group, and hs-CRP levels were also lower in the PELD group, though statistically significant only on the 3rd postoperative day. The surgery duration and incision length were shorter in the PELD group. Complication rates were low, with two complications in the MLD group and one in the PELD group. Conclusion: Both MLD and PELD demonstrated positive outcomes in terms of pain and functional disability reduction, but PELD showed advantages in terms of shorter surgery duration, smaller incision length, and lower levels of certain inflammatory markers. No significant difference was noted in clinical outcomes between MLD and PELD. Postoperative systemic cytokine response is significantly lower in the PELD group than in the MLD group.